Patient and family updates in a district hospital: a QI project - Kimberly Lim Xinyi; Divya Kanakalingam; Jegadis Sreeneyasan (Future Healthcare Journal)
Background and introduction: Involvement of family members could impact patient outcome and quality of care in a beneficial way because having family members updated regularly could improve the relationship between clinicians, patients, and family members.1–3 Cultivating positive rapport with family members could also improve quality of care for both patients who have capacity and those under Deprivation of Liberty Safeguards (DOLS).4,5 Unintentionally, we may have neglected the importance of family updates, especially on a busy day during ward rounds. Aims and objectives: This quality improvement project aimed to update family members regularly and improve the relationship between clinicians, patients, and their family members, to help promote patient satisfaction and safety. The main aim was for 100% of patients, with or without capacity, to have their family members involved and updated at least twice a week within 12 months. Methodology: A survey was distributed across medical and surgical departments to explore patients’ perspectives on patient and family updates of clinical progress. Following this, patients’ data were collected from the electronic system on the following variables: (1) family members who were updated within 48 h; (2) family members who were updated within 1 week; and (3) information provided during family updates. Two plan–do–study–act (PDSA) cycles were conducted over a period of 6 months. ‘Relative Progress Notes’ on the electronic system were extracted and analysed. Results: Of 51 patients who answered the survey, 88.2% had updates regarding their clinical progress daily. However, 51.0% of patients had not been asked by the doctors if they would like their family members updated. In addition, 54.9% of patients expressed that they would like their family members to be updated daily, 37.3% wanted family updates to be every 2 to 3 days, and 7.8% wanted updates to be weekly. Furthermore, 76.5% of patients who did not have capacity wanted their family members to be updated daily, whereas 23.5% of such wanted their family members to be updated every 2 to 3 days.By contrast, of 46 patients in second cycle, relatives of 28.2% were updated within 48 h compared with 22.9% during the first cycle. Furthermore, relatives of 54.3% of patients were updated within 1 week during the second cycle compared with 25.0% during the first cycle. While there was a reduction in the number of patients under DOLS who had their relatives updated within 48 h, relatives of 52.2% of patients were updated within 1 week during the second cycle compared with 26.1% during the first cycle. Overall, there was an improvement in the information provided during family updates, including condition, diagnosis, management and follow-up. Interventions implemented were posters, departmental teaching sessions, mass emails to junior doctors and appointing of family update ambassadors. Conclusion: In conclusion, this project highlights the need to ensure that patients and family members are updated regularly, especially for those patients who lack capacity. Family involvement is likely to improve patient satisfaction and, thus, should be encouraged across NHS settings.